What Have We Learned about Household Biomass Cooking in Central America? - Wang, Xiaoping; Franco, Janina; Masera, Omar R.; Troncoso, Karin; Rivera, Marta X. (World Bank, Washington, DC, 2016)
Twenty million people in Central America cook with biomass using open fires or rudimentary stoves. The number of people using biomass for cooking in the region will remain significant for a long time due to high incidence of poverty, high Liquid Petroleum Gas (LPG) prices coupled with unsustainable LPG subsidies, as well as relatively easy access to fuel wood in the region. Providing these people with clean and efficient cooking solutions is not just an energy issue, but one related to poverty, gender inequality, public health, environmental sustainability, local employment, climate change, agriculture, and local employment. A new generation of improved biomass cook stoves (ICS) has recently become available in Central America. The economic benefits from improving public health, reducing deforestation, and mitigating greenhouse gas emissions well outweigh the costs of ICS dissemination. Efforts involving donor agencies, governments, non-governmental organizations, as well as local entrepreneurs have been made to disseminate ICS in the region in the last 10 years. The objective of this study is to better understand current developments in clean and efficient biomass cooking solutions, factors that have precluded a larger penetration of ICS within the region, and lessons learned from past programs-both in the region and in other countries-that may be relevant to Central America. The study recommends key actions that may help the region step up its current dissemination efforts and promote sustained use of ICS, a first step toward universal access to ICS by fuel wood users. Its intended audience includes different stakeholders, including government agencies, regional and international organizations, as well as various implementing entities who are thinking or rethinking appropriate technologies, policy interventions, financing, and delivery mechanisms for Central America to promote ICS.